PENDAMPINGAN KEPADA PASIEN TERMINAL - Julita Tuamely (IAKN Ambon, 2019)
Death is the final stage of life. death can come suddenly without warning or follow a long period of illness. Sometimes death strikes the young but always awaits the old. Assistance to patients who will die must still be done. Comprehensive care for the dying person rarely demands more than careful symptom management and attention to the basic physical needs of the patient as a person and as a family. In addition to addressing symptom management, palliative care and hospice interventions can be aimed at helping a person achieve feelings of well-being in the social and interpersonal dimensions, to build or deepen feelings of meaning and discover their own unique feelings in the meaning of life. The most basic thing is, the companion can serve in a way that is fully present. Perhaps we have no more answers to existential questions about life and death than do people who are dying. Maybe we can't reduce all the feelings of regret and fear facing ignorance. However, it is not our job to answer all these problems. The main task of a caretaker is to stand by the patient, continuously providing the necessary physical and psychosocial assistance, while the patient himself struggles to find answers.